2018
DOI: 10.1021/acs.orglett.8b02785
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Atropoenantioselective Synthesis of Axial Biaryls via Reductive Amination and Dynamic Kinetic Resolution

Abstract: The unprecedented ruthenium-catalyzed atropoenantioselective reductive amination of aldehydes with alkylamines via a cascade transfer hydrogenation and dynamic kinetic resolution strategy is described. This protocol features broad substrate scope and good functional group tolerance and allows the rapid assembly of axially chiral biaryls in good to high yields with high to excellent enantioselectivities. In addition, such structural motifs may have potential applications in enantioselective catalysis as chiral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…However, it is possible for atropisomers of the carbaldehyde starting materials and the dehydrated toluenesulfonimide intermediates to easily interconvert into each other via the formations of bridged biaryl lactol intermediates 1a′ and 4a′ (Fig. 3c ) 40 46 . As a technical note, the formation of the biaryl lactol intermediate 1a′ can be evidenced via 1 H NMR analysis on the basic solution of the 2-arylbenzaldehyde 1a (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is possible for atropisomers of the carbaldehyde starting materials and the dehydrated toluenesulfonimide intermediates to easily interconvert into each other via the formations of bridged biaryl lactol intermediates 1a′ and 4a′ (Fig. 3c ) 40 46 . As a technical note, the formation of the biaryl lactol intermediate 1a′ can be evidenced via 1 H NMR analysis on the basic solution of the 2-arylbenzaldehyde 1a (see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the same authors reported in parallel a Ru-catalysed atroposelective reductive amination via dynamic kinetic resolution (Scheme 17C). 43 This methodology expanded the scope to both primary and secondary alkyl amines leading to a variety of amino alcohols in good to excellent yields and enantioselectivities.…”
Section: Scheme 15mentioning
confidence: 99%
“…The “lactone concept” developed by Bringmann and co-workers first exploited the lability of biaryl lactones in transesterification reactions, finding numerous applications in the synthesis of natural products and bioactive substances. , Efficient catalytic variants of this strategy made use of Co-, Ir-, and Cu-catalyzed reductions and a transesterification reaction using a bifunctional thiourea catalyst (Scheme A). More recently, the groups of Akiyama and Wang described a related DKR strategy for the asymmetric reductive ring opening of configurationally labile biaryl hemiaminal ethers (Scheme B). Inspired by these studies, we envisioned that related biaryl hemiaminals with the structure 1 (Scheme C) should also be configurationally labile and, therefore, could be suitable starting materials for the atroposelective synthesis of axially chiral diamines, homologues of BINAM, after an asymmetric reductive amination process.…”
Section: Introductionmentioning
confidence: 99%